Thief strikes! - Lysiak, Hilde; Lysiak, Matthew (New York, NY Branches/Scholastic Inc, 2019)
Crime reporter Hilde Lysiak always gets the scoop! Special tomato plants were stolen from a local greenhouse! Hilde wants to catch the thief. So she and her sister Izzy start interviewing witnesses. But they soon discover that people all around town are getting sick! Can this real-life reporter get to the root of these two mysteries?"--Page [4] of cover
English stories
2
Keywords: Reporters and reporting -- Juvenile fiction; Theft -- Juvenile fiction